1992
DOI: 10.1002/jso.2930490305
|View full text |Cite
|
Sign up to set email alerts
|

Alpha‐fetoprotein production by hepatocellular carcinoma is prognostic of poor patients survival

Abstract: Immunohistochemistry using the avidin-biotin-peroxidase complex method was performed to study the production of alpha-fetoprotein (AFP) in hepatocellular carcinoma (HCC) tissue specimens which were obtained surgically. The relationship between staining for AFP and serum AFP levels or pathological findings was examined. The prognosis of the patients with HCC who underwent curative hepatic resections was studied with respect to the staining for AFP in their tumors. The mean serum AFP level in patients with posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 12 publications
(7 reference statements)
3
17
0
Order By: Relevance
“…Except for the AFP level, our results were the same as those in the report by Ando et al 27 Previous reports have demonstrated that AFP is one of the prognostic factors in patients with HCC. [32][33][34][35] The importance of the AFP level as a prognostic factor for HCC has been shown in a report from the Center of the Liver Italian Program (CLIP) investigators. 2 Hanazaki et al 36 reported, similarly to our result, that an AFP value of 1000 ng/ml or more was an independent unfavorable factor affecting survival after hepatic resection for HCC with hepatitis C virus infection.…”
Section: Discussionmentioning
confidence: 95%
“…Except for the AFP level, our results were the same as those in the report by Ando et al 27 Previous reports have demonstrated that AFP is one of the prognostic factors in patients with HCC. [32][33][34][35] The importance of the AFP level as a prognostic factor for HCC has been shown in a report from the Center of the Liver Italian Program (CLIP) investigators. 2 Hanazaki et al 36 reported, similarly to our result, that an AFP value of 1000 ng/ml or more was an independent unfavorable factor affecting survival after hepatic resection for HCC with hepatitis C virus infection.…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, an examination of the characteristics of patients with HCC who had the T1653 mutation showed that an elevated a-fetoprotein level (у300 ng/mL) was the only predictor for the development of HCC in patients with the T1653 mutation. It has been reported that a-fetoprotein level is useful not only for diagnosis but also as a prognostic indicator for patients with HCC [22,23], suggesting that the T1653 mutation might be associated with poor prognosis for patients with HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Normally produced by the fetal yolk sac, liver, and intestine, elevated levels can be associated with HCC in the appropriate clinical setting [11]. Previous studies have documented that the level of AFP at diagnosis may be predictive of patient survival [12][13][14][15]. The specificity for the diagnosis of HCC has been estimated at roughly 91%, based on a reference value of Ͻ20 ng/ml.…”
Section: Introductionmentioning
confidence: 99%